2000
DOI: 10.1902/jop.2000.71.4.562
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Pathogenic Periodontal Microflora in Healthy Young Adult Smokers

Abstract: These data indicate that the prevalence of colonization of the sulcus by pathogenic bacterial species in periodontitis-free individuals is related to the quantity and duration of cigarette smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 42 publications
5
50
0
5
Order By: Relevance
“…The present study found no correlation between smoking and the prevalence of the five tested bacteria. It is true that Shiloah et al (27) showed that the prevalence of pathogenic bacteria in the periodontal sulcus of periodontitis-free individuals is related to their daily consumption of cigarettes and duration of cigarette smoking. However, it is not realistic to monitor the daily consumption of cigarettes by younger smokers, even if this factor may affect the early colonization by periodontal pathogens in the periodontal sulcus of those in the younger populations.…”
Section: Vol 46 2008 Age For Initial Colonization Of Periodontal Pamentioning
confidence: 99%
“…The present study found no correlation between smoking and the prevalence of the five tested bacteria. It is true that Shiloah et al (27) showed that the prevalence of pathogenic bacteria in the periodontal sulcus of periodontitis-free individuals is related to their daily consumption of cigarettes and duration of cigarette smoking. However, it is not realistic to monitor the daily consumption of cigarettes by younger smokers, even if this factor may affect the early colonization by periodontal pathogens in the periodontal sulcus of those in the younger populations.…”
Section: Vol 46 2008 Age For Initial Colonization Of Periodontal Pamentioning
confidence: 99%
“…These irritants cause white lesions. Smoking can also cause abnormalities in the oral cavity such as the tongue, gums, mouth mucosa, teeth and palate in the form of nicotine stomatitis and fungal infections [19,20]. All of these factors can cause DNA damage [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoke has been shown to cause shifts in the microbial species that comprise dental plaque (Haffajee & Socransky 2001, Kamma et al 1999, Shiloah et al 2000, Umeda et al 1998, van Winkelhoff et al 2001, Zambon et al 1996. In a recent study by our group , it was hypothesized that tobacco may induce alterations to the molecular structure of lipid A in a manner consistent with reduced inflammatory potential.…”
Section: Introductionmentioning
confidence: 99%